Effects of ocean acidification and salinity variations on the physiology of osmoregulating and osmoconforming crustaceans - Ramaglia, Andressa Cristina [UNESP]; de Castro, Leandro Mantovani [UNESP]; Augusto, Alessandra [UNESP] (Springer Nature, 2018)
Survival, osmoregulatory pattern, oxygen consumption, energy spent on metabolism, ammonia excretion, type of oxidized energy substrate, and hepatosomatic index were evaluated in decapods (an osmoregulating crab, Callinectes danae, and an osmoconforming seabob shrimp, Xiphopenaeus kroyeri) exposed to carbon dioxide-induced water acidification (pH 7.3, control pH 8.0) and different salinities (20, 25, 30, 35, and 40‰) for 3 days. Compared to the animals kept at controlled pH, exposure to reduced pH resulted in the loss of osmoregulatory capacity in C. danae at all salinities, except for some hyporegulation at 40‰, and reduced oxygen consumption and ammonia excretion at 20 and 40‰. Xiphopenaeus kroyeri remained an osmoconformer in all evaluated conditions, except for some hyporegulation at 40‰, and when exposed to the reduced pH, it presented changes in oxygen consumption at all salinities and reductions in ammonia excretion at 20 and 35‰ compared to the control animals. Both species use protein as the main energy substrate and decrease the hepatosomatic index when exposed to reduced pH relative to the control. The observed changes may be associated with changes in the activity of enzymes related to osmoregulation, the use of amino acids as osmotic effectors of cell volume control and recovery, and the Bohr effect, and, because the gills are multifunctional organs related to osmoregulation, the changes may be related to acid–base control, nitrogen excretion, and respiration, with a change in one of these functions bringing about changes in the others.
Keywords: Acidification; Callinectes; Climate change; Fishery; Osmoregulation; Xiphopenaeus